The Role of Self Esteem in Moderating the Influence of Discount Prices on Purchase Intention - Aurora Yesaya Luhulima; Putu Saroyini Piartrini (International Journal of Economics and Management Sciences, 2024)
This research aims to explain the influence of discount prices on the intention to purchase ZARA store products in Denpasar City, the influence of self-esteem on the intention to purchase ZARA stores in Denpasar City, the role of self-esteem in moderating the role of discount prices on purchase intentions. This research was conducted in Denpasar City with a sample of 160 respondents who knew about the ZARA brand but had never made a purchase or transaction with a minimum of high school/equivalent education. The data analysis techniques used in this research are descriptive analysis, classical assumption testing and inferential analysis in the form of Moderate Regression Analysis (MRA). The results of this research show that discount prices have a positive and significant effect on the intention to buy products from the ZARA brand, self-esteem has a positive and significant effect on the intention to buy products from the ZARA brand, the interaction of discount prices and self-esteem has a positive and significant effect on the intention to buy ZARA brand products. The theoretical implications of this research can strengthen the relationship with previous research which investigated the relationship between discount prices and self-esteem on purchase intentions. In addition, it was found that self-esteem plays a moderator role that strengthens the influence of discount prices on purchase intentions. Positive and significant practical implications, especially for the ZARA brand. It is hoped that this research will be able to provide additional references regarding achieving profits and increasing sales of products from the ZARA brand, so that it can increase consumers' purchasing intentions to buy and use products from the ZARA brand.